Persepsi Pengguna Terhadap Kinerja Pelayanan BRT Trans Semarang - Ovi Letare Monalisa Sinaga; Widjonarko Widjonarko (Teknik PWK (Perencanaan Wilayah Kota), 2020)
BRT Trans Semarang is an alternativ     e solution to reduce private vehicles in Semarang City. In order to improve the services of BRT it is important the customer satisfaction for using BRT. Customer Satisfaction index is an instrument to measure the performance of BRT. The quality of service which is using customer satisfaction index include reliability, convenience, comfort and cleanliness, security and safety. The analysis show the performance of BRT’s Semarang city is good indicated by Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The analysis by Customer Satisfaction Index (CSI) show a result 79%. The level of service is show the services of BRT Trans Semarang has high quality in reliability, convenience, comfort and cleanliness, security and safety. The performance of the BRT of Trans Semarang service is important to always improve. This needs to maintain user satisfaction with the BRT of Trans Semarang BRT. Based on an evaluation of the technical performance and the results of the Importance Performance Analysis (IPA) show the several quality of services should be priorities to improvement are the standing space and seating for passengers, improvement in the driver/driver attitude when driving BRT, the improvement in the attitude of officers when serving passengers and the ease for passengers to get BRT both when peak hour and off peak hour hours and after work and then the convenience for passengers to get the latest information about route changes.